Physiological and mechanical indices serving the new cross-country olympic mountain bike performance - Hays, A.; Nicol, C.; Bertin, D.; Hardouin, R.; Brisswalter, J. (International Journal of Sports Physiology and Performance, 2021)
Objectives: To identify relevant physiological, mechanical, and strength indices to improve the evaluation of elite mountain bike riders competing in the current Cross-Country Olympic (XCO) format.